PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DI SEKRETARIAT DPRK ACEH UTARA - Iba, Zainuddin (JURNAL KEBANGSAAN, 2018)
The purpose of this study was to analyze the effect of work motivation on employee performance and the influence of the work environment on employee performance at the North Aceh DPRK Secretariat. The results of the analysis were obtained; a) The level of achievement of work motivation of employees of the North Aceh DPRK Secretariat, amounting to 80.67%. From these results it almost shows the optimal level of work motivation. b) The level of achievement of the work environment in supporting employee work, amounting to 81.71%. From these results it has shown a good level, although it can still be optimized again. c) From the Regression analysis it is known that there is an effect of employee motivation and work environment on employee performance with the relationship model of both variables are: Y = 32,623 + 0,217 X1 + 1,071 X2 (X1 = Work motivation, X2 = Work environment). The correlation magnitude between the variables of work motivation (X1) on performance (Y) is 0.859. Which states that the motivation contribution to performance is: 73.79%. While the correlation between work environment variables (X2) to performance (Y) is: 0.953. Which states the contribution of the work environment to employee performance is 90.82%. Based on the regression analysis between motivation and organizational climate on employee performance states a). if work motivation increases by 10 percent, then performance will increase by 2.17 percent. b). If work environment support increases by 10 percent, then employee performance will increase by 10.71 percent. c). The influence of the work environment is higher than work motivation. Keywords: Work Motivation, Work Environment, Employee Performance.